Use of the land and the elements of agricultural technology for maize in the Morelia-Queréndaro Valley - Franco Gaona, Arturo; Ramírez-Valverde, Benito; Cruz León, Artemio; Sangerman-Jarquín, Dora Ma.; Juárez Sánchez, José Pedro; Ramírez Valverde, Gustavo (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of this work is to know the use of land and the elements of agricultural technology (ETA) that is used in the cultivation of corn at the community level and the participation of public and private institutions in the promotion and employment of the ETA in the cultivation of corn, in the communities of The Troje (Álvaro Obregón) and Cañada of the Sauces (Tarímbaro), Michoacán, Mexico. A Random Stratified Sampling with 57 interviews with corn producers was used. It was found in the communities can be used five elements of agricultural technology: biological, chemical, mechanical-computer, agronomic and water in a differentiated way; whose use is subject to the topographic conditions of the cultivation terrain, availability of economic resources, diffusion, quality, presence at the community and cultural level and for the promotion made by public and private institutions, based on the type of agriculture that is practice in the community: traditional or modern.
Keywords: agricultural paradigm; peasant; traditional and modern agriculture